Corporate Social Responsibility Communication Strategy of Pertamina Subholding Upstream Regional Java in Enhancing Corporate Image - Azza, Aulia; Saleh, Amiruddin (IJESS International Journal of Education and Social Science, 2025)
This study aims to analyze the communication strategies implemented by the Communication, Relations, & Community Involvement and Development (CID) Team of Pertamina Subholding Upstream Regional Java in carrying out Corporate Social Responsibility (CSR) programs to shape and strengthen the company’s image amidst social dynamics and high public expectations. This research employs a qualitative descriptive approach and refers to the four-phase public relations communication strategy model by Cutlip et al. (2016), which includes fact finding, planning and programming, taking action and communicating, and evaluating the problem. Data were collected through in depth interviews, field observations, and document analysis. The findings show that a structured, collaborative, and sustainable communication strategy effectively promotes active public engagement and increases community satisfaction with the CSR programs. Programs such as Pendidikan Lingkungan untuk Anak (PELITA) and other initiatives are implemented through a multiyear approach and widely disseminated via conventional media, mass media, and social media platforms. Program evaluations are carried out using tools such as Social Return on Investment (SROI) and the Community Satisfaction Index (IKM), which demonstrate that CSR programs not only create significant social impact but also enhance the company’s reputation. Open and participatory two-way communication proves to be the key to the success of these strategies. The study concludes that strategically implemented CSR serves not only as a form of corporate social responsibility but also as a vital instrument for building public trust and legitimacy.